Prevalence and predictors of anemia among HIV-positive women in Ethiopia: findings from the Ethiopian demographic and health survey - Getie, Michael; Belay, Gizeaddis; Deress, Teshiwal (Frontiers in Medicine, 2025)
BackgroundAnemia is a significant health issue among HIV-positive women in Ethiopia, adversely affecting their quality of life and disease progression. Limited data exist on the prevalence and associated factors of anemia in this population. This study aimed to investigate the prevalence and predictors of anemia among HIV-positive women in Ethiopia using data from the Ethiopian Demographic and Health Surveys.MethodsA cross-sectional study design was employed using data from the Ethiopian Demographic and Health Survey, which included HIV-positive women aged 15–49 years. Variables with a p-value ≤ 0.25 in the bivariable logistic regression model were incorporated into the multivariable logistic regression analysis, along with a 95% confidence interval and Odds Ratio, to assess the association between anemia and independent variables. A p-value ≤ 0.05 was deemed statistically significant.ResultsThe analysis included a weighted sample of 571 HIV-positive women of reproductive age from three survey rounds. The overall prevalence of anemia among HIV-positive women was 23.9% (95% CI: 19.24–29.24). The prevalence varied significantly by region, with the highest rates in small peripheral regions (31.2%). Several predictor variables were identified, including low body mass index (BMI < 18.5) (AOR = 2.9; 95% CI: 1.21–9.70; p = 0.031), female-headed households (AOR = 4.5; 95% CI: 1.14–11.25; p = 0.032), lack of iron utilization during pregnancy (AOR = 2.9; 95% CI: 1.48–9.32; p = 0.040), and the use of unimproved toilet facilities (AOR = 1.6; 95% CI: 1.18–6.87; p = 0.021).ConclusionThis study found that nearly one in four HIV-positive women of reproductive age in Ethiopia is affected by anemia, with regional disparities and multiple contributing factors. Therefore, it is a critical public health problem in the area. To enhance the health and well-being of HIV-positive women in Ethiopia, urgent need for interventions targeting nutritional support, maternal care, and sanitation access are essential.